Correlation of IL-1β Level and Body Temperature to the Severity of Acute Respiratory Distress Syndrome (ARDS) and Mortality in COVID-19 Patients - Andriani, Inge; Utariani, Arie; Hamzah, Hamzah (Faculty of Medicine-Universitas Airlangga, 2022)
Introduction: IL-1β and IL-6 are cytokines that have major roles in cytokine storms and endogenous pyrogens. Several studies have also displayed the effectiveness of IL-1β inhibitors in COVID-19 patients in minimizing severity and mortality. Objective: This study aims to analyze the correlation between IL-1β and body temperature with ARDS severity and mortality in COVID-19 patients. Methods: This is an analytical observational study with a prospective cohort design. A total of 54 patients have met the inclusion criteria from July to September 2020. This study mainly applied the Spearman-Rho, Mann Whitney, free sample T2 test, and Chi-Square test. Results: The correlation between body temperature and IL-1β levels in COVID-19 patients with ARDS did not show a statistically significant difference towards mortality and ARDS severity, as shown by the p-value > 0.05 in the analysis tests of each of the variables studied. Nonetheless, the occurrence of ARDS (p = 0.022), the severity of ARDS (p = 0.001), application of mechanical ventilation (p = 0.00), secondary infection (p = 0.00), and length of stay (p = 0.042) were found to be statistically significant towards COVID-19 patients' mortality. Conclusion: Body temperature does not correlate with the occurrence of ARDS, the severity of ARDS, mortality, and IL-1β levels. IL-1β levels and transformation in IL-1β levels also do not correlate with mortality as well as the occurrence and severity of ARDS, but the use of mechanical ventilation, secondary infection, and length of stay were correlated with mortality in COVID-19 patients.